Protective Effects of Bariatric Surgery on Kidney Functions by Inhibiting Oxidative Stress Responses Through Activating PPARα in Rats With Diabetes - Jiang, Hong-Wei; Zhou, Yong; Zhou, Pin-Yi; Zhang, Tian-Yi; Hu, Jing-Yao; Bai, Xue-Tao (Frontiers in Physiology, 2021)
Objective: The aim of this study is to explore the protective effects and the regulatory mechanisms of bariatric surgery on kidney injury in diabetic rats. Methods: We established a useful type 2 diabetic rat model using high-fat and high-sugar diet feeding following low-dose STZ treatment. Sprague-Dawley (SD) rats were randomly divided into the following groups: Control (Con) group, diabetic nephropathy (DN) group and Duodenal-jejunal bypass surgery (DJB) group. The food intake and body weight of rats were monitored, and the glucose tolerance test (OGTT) test was performed every 2 weeks. Glomerular filtration rate (GFR) and urinary albumin excretion rate (UAFR) were measured to assess renal function. H&E, PAS and Masson staining were used to evaluate renal histopathological changes. TUNEL assay was performed to detect the cell apoptosis. The expression of oxidative stress factors and inflammatory factors in renal tissues of rats was detected by ELISA. The expression of PPARα, ROS and NF-κB was detected by immunofluorescence. For in vitro experiment，HK2 cells cultured with high glucose were treated with PPARα agonist, PPARα antagonist and Adenosine 5’-monophosphate (AMP)-activated protein kinase (AMPK) agonist, respectively. The expression of AMPK/PPARα/NF-κB signaling pathway related proteins were detected by Western blot. Results: Bariatric surgery improved the glucose tolerance of DN rats. The GFR was decreased, the promotion of UAER was inhibited, and the renal injury was alleviated. The extracellular matrix fraction was decreased, and the renal function was improved. Meanwhile bariatric surgery activates PPARα, inhibits ROS release, reduces oxidative stress injury, and reduces renal cell apoptosis. In vitro experiments results showed that AMPK activator could activate PPARα, down-regulate NF-κB, and inhibit inflammatory response. The phosphorylation of AMPK was inhibited by PPARα antagonism. Conclusion: Bariatric surgery can activate PPARα, inhibit oxidative stress injury, improve glucose metabolism and renal function in DN rats.